Comparison of the effect of regular coupling beam and coupling beam with crown on the response and behavior of shear walls in medium-rise buildings - حبقه هبه; أكرم صقور (Latakia University Journal -Engineering Sciences Series, 2022)
Reinforced concrete shear walls with coupling beams are used in many buildings as resisting elements to horizontal loads caused by earthquake or wind. Shear walls with openings are called coupled shear walls which act as cantilevered shear walls joined by coupling beams. Openings for windows and doors affect the behavior of the structure and cause to decrease the strength of shear wall. The aim of this research is to study the behavior of coupled shear walls with regular coupling beams / with crowns, to understand seismic response and compare them, to reduce the damage in the building under the influence of earthquake, and increase its stiffness, and facilitate the maintenance process after the earthquake. A study was carried out using (ETABS) program and a nonlinear static analysis was procedure on two models of buildings consisting of eight stories, where the first model consists of shear walls with traditional coupling beams and the second of shear walls with coupling beams with crowns. The models were compared in terms of base shear, axial forces, coupling ratios, Von mises stresses, and locations of plastic hinges. The results of the analysis clearly showed the importance of using coupling beams with crowns, because it leads to an increase in the resistance of the nodes to the meeting of the beams with the wings of the shear walls with an opening, in addition to an increase in the bearing capacity of the building and the shear walls.